Differential ionization in antiproton–hydrogen collisions within the convergent-close-coupling approach. - Abdurakhmanov, Ilkhom; Kadyrov, Alisher; Bray, Igor; Stelbovics, Andris (Institute of Physics Publishing Ltd., 2011)
A recently developed fully quantal convergent-close-coupling (CCC) approach (Abdurakhmanov et al 2011 J. Phys. B: At. Mol. Opt. Phys. 44 075204) to ion–atom collisions is extended to differential ionization studies. An important feature of the method is that it does not have classical limitations on the relative motion of participating particles. The approach is applied to calculate fully differential, as well as various doubly and singly differential cross sections of ionization in antiproton collisions with atomic hydrogen. The CCC results for various differential cross sections agree reasonably well with the results of the semiclassical CC and the continuum-distorted-wave-eikonal-initial-state approaches,particularly at high energies. However, some discrepancies exist at low energies, where the final state interactions among colliding particles are found to be very important.